2019
DOI: 10.3389/fvets.2019.00175
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic and Phenotypic Characterization of the Etiological Agent of Canine Orchiepididymitis Smooth Brucella sp. BCCN84.3

Abstract: Members of the genus Brucella cluster in two phylogenetic groups: classical and non-classical species. The former group is composed of Brucella species that cause disease in mammals, including humans. A Brucella species, labeled as Brucella sp. BCCN84.3, was isolated from the testes of a Saint Bernard dog suffering orchiepididymitis, in Costa Rica. Following standard microbiological methods, the bacterium was first defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…This strain displayed distinctive biochemical properties and a unique SDS-PAGE protein profile [ 82 ]. This isolate was initially identified under experts’ hands as B. melitensis biovar 2, afterward as an atypical B. suis [ 77 ]. MLVA-16, WGS, and detailed phenotypic characterization identified the Brucella sp.…”
Section: Expanding the Number Of Brucella Specimentioning
confidence: 99%
See 2 more Smart Citations
“…This strain displayed distinctive biochemical properties and a unique SDS-PAGE protein profile [ 82 ]. This isolate was initially identified under experts’ hands as B. melitensis biovar 2, afterward as an atypical B. suis [ 77 ]. MLVA-16, WGS, and detailed phenotypic characterization identified the Brucella sp.…”
Section: Expanding the Number Of Brucella Specimentioning
confidence: 99%
“…MLVA-16, WGS, and detailed phenotypic characterization identified the Brucella sp. BCCN84.3 as distinct species, after 35 years of its isolation [ 77 ]. Due to their broader metabolic alternatives, non-classical Brucella isolates from humans were initially identified as Ochrobactrum spp.…”
Section: Expanding the Number Of Brucella Specimentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, additional species have been described, with the genus expanding to include B. pinnipedialis and B. ceti isolated from marine mammals ( Foster et al, 2007 ), B. microti from voles ( Scholz et al, 2008b ), B. inopinata isolated from a human infection ( Scholz et al, 2010 ), B. papionis from baboons ( Whatmore et al, 2014 ) and B. vulpis , isolated from foxes ( Scholz et al, 2016a ). Additionally, a number of novel atypical strains from human and other mammalian hosts have been described, but await formal classification ( Tiller et al, 2010a , b ; Guzmán-Verri et al, 2019 ). These species and strains reflect an ongoing expansion of the known host range and genetic diversity of the genus.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies demonstrated that the low economical profit of small farms, limitation of veterinary support and minimal education/training of farmers may contribute to the persistence of risk factors (Asinamai et al., 2018; Beauvais et al., 2016; Coelho et al., 2019). Furthermore, as shown in the current study, B. melitensis biovar 2 can infect dogs and circulates between farms, playing an important role in the human contamination (Forbes, 1990; Guzmán‐Verri et al, 2019; Rezaei‐Sadaghiani et al., 1996). The infection of dogs with B. suis , B. melitensis and B. abortus has been shown in both field and experimental studies.…”
Section: Discussionmentioning
confidence: 57%